A Design of Security Oriented Mobile Robot Control System - YAN Yi-xin; ZHANG Yang (Journal of Harbin University of Science and Technology)
In view of the existing problems in the control system of security robots, such as the function extension is limited by the load capacity of the main control machine of the robot, the monitoring platform does not support map loading, or the map updates are poor in real time, etc, the paper designed a control system for security robot The system designs the hardware structure of the robot by using decentralized modular scheme to enhance load capacity of the main control machineBased on the research of LidarSLAM technology, a map coordinate matching algorithm is proposed Then, a mobile robot monitoring platform is built by using web development technology, and the validity of the map loading method and the realtime of map updating are verified on this platform The system effectively solves the shortcomings of the existing security robot control system, and reduces the maintenance cost of the system It provides a reference for the design of the security robot control system